PRINCIPLE OF SUPERPOSITION AT CONSTRUCTION OF GEOLOGIC-GENETIC MODELS OF GOLD-ORE SYSTEMS OF UKRAINIAN SHIELD - Dragomyretsky, O.; Kadurin, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Method of geologic-genetic interpretation of geological information on the ore-deposit objects of USCH implies at first the construction of simple geologic-genetic models and then their successive superposition regarding possible combinations of different geological conditions. It permits to decode the peculiarities of formation of ore-deposit systems. Simple models are characterized by hierarchically lined up boundary conditions: power features, origin, genesis and paragenesis.